1989
DOI: 10.1007/bf00934524
|View full text |Cite
|
Sign up to set email alerts
|

Precocious appearance of markers of squamous differentiation in metaplastic cells of human endocervix

Abstract: We used immunoperoxidase methods employing antibodies against involucrin and filaggrin, both markers of squamous terminal differentiation, to study squamous metaplastic transformation in the human endocervix. Expression of involucrin and filaggrin was restricted to squamous metaplastic cells whereas columnar epithelial cells were constantly negative. Immature squamous metaplastic epithelium also showed a positive immunostaining. In mature squamous metaplasia a suprabasal homogeneous staining pattern similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…These findings are consistent with the work of others suggesting that SM occurs through the increased recruitment of basal cells into an amplifying population of committed squamous lineage cells (29). This amplifying population occupies the suprabasal layer and expresses involucrin, keratin 6B, and keratin 14, which are known markers of actively proliferating suprabasal cells in normal squamous mucosa, SM either in the lung or other mucosal sites, and the epidermis at the edge of wounds (29,30,(45)(46)(47).…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with the work of others suggesting that SM occurs through the increased recruitment of basal cells into an amplifying population of committed squamous lineage cells (29). This amplifying population occupies the suprabasal layer and expresses involucrin, keratin 6B, and keratin 14, which are known markers of actively proliferating suprabasal cells in normal squamous mucosa, SM either in the lung or other mucosal sites, and the epidermis at the edge of wounds (29,30,(45)(46)(47).…”
Section: Discussionsupporting
confidence: 90%
“…Lara et al [ 7 ] studied 87 cervical biopsies, classifi ed as either normal cervical epithelium, nonneoplastic lesions, preneoplastic lesions, or neoplastic lesions, and performed fi laggrin protein immunostaining. Non-squamous epithelium, either benign or malignant, showed lack of fi laggrin expression as also demonstrated elsewhere [ 8 ]. As for normal squamous epithelium, they found the aforementioned homogeneous suprabasal pattern.…”
Section: Filaggrin and The Cervixsupporting
confidence: 69%
“…Changes in fi laggrin/pro-fi laggrin expression were related to abnormal keratinization rather than to the presence of HPV DNA or type. With regard to the T-zone, Serra et al [ 8 ] showed that fi laggrin was completely absent from the endocervical columnar epithelium, but with diffuse and intense immunoreactivity even in the most immature metaplastic epithelium. In the area of very incipient squamous metaplasia, unnoticed histologically, fi laggrin expression was found to be restricted to the reserve subcolumnar cells, which is thought to play a role in the histogenesis of the T-zone [ 8 , 81 ].…”
Section: Filaggrin and The Cervixmentioning
confidence: 99%
“…Hormonal and growth factor alterations may induce hyperplasia or squamous metaplasia within the prostate basal layer [15,33,34]. To investigate this possibility, PrECs and prostate specimens were stained with an antibody against involucrin, a protein associated with squamous differentiation/metaplasia [27,35]. Formalin-fixed, paraffin-embedded blocks of proliferating PrECs stained strongly for involucrin in vitro ( Fig.…”
Section: Involucrin Expression Within Prec and Normal Prostatementioning
confidence: 99%